Light backscattering properties of distorted hexagonal atmospheric ice particles within the physical optics approximation - Timofeev, Dmitriy N.; Konoshonkin, Alexander V.; Kustova, Natalia V.; Shishko, Viсtor A. (Atmospheric and oceanic optics)
Light backscattering matrices are calculated within the physical optics approximation for hexagonal atmospheric ice particles distorted in different ways for the case of arbitrary spatial orientation and single scattering. A hexagonal prism with a height of 31.62 mu m and an external diameter of 22.14 mu m, which is typical for column-type particles observed in cirrus clouds, is chosen as a basic geometric shape. Three shape distortion methods for the particles are used: tilt, convexity and concavity; the angle of distortion varies from 0 degrees to 50 degrees for every particle type. The wavelength of incident radiation is 1.064 mu m. The calculation has shown a sharp decrease in the backscattering cross section with an increase in the angle of distortion for all particle types under study.